An assessment of the lattice strain in the CrMnFeCoNi high-entropy alloy. (1st January 2017) - Owen, L.R.; Pickering, E.J.; Playford, H.Y.; Stone, H.J.; Tucker, M.G.; Jones, N.G.
Abstract: The formation of single phase solid solutions from combinations of multiple principal elements, with differing atomic radii, has led to the suggestion that the lattices of high-entropy alloys (HEAs) must be severely distorted. To assess this hypothesis, total scattering measurements using neutron radiation have been performed on the CrMnFeCoNi alloy and compared with similar data from five compositionally simpler materials within the same system. The Bragg diffraction patterns from all of the studied materials were similar, consistent with a face-centered cubic structure, and none showed the pronounced dampening that would be expected from a highly distorted lattice. A more detailed evaluation of the local lattice strain was made by considering the first six coordination shells in the pair distribution functions (PDF), obtained from the total scattering data. Across this range, the HEA exhibited the broadest PDF peaks but these widths were not disproportionately larger than those of the simpler alloys. In addition, of all the materials considered, the HEA was at the highest homologous temperature, and hence the thermal vibrations of the atoms would be greatest. Consequently, the level of local lattice strain required to rationalise a given PDF peak width would be reduced. As a result, the data presented in this study do not indicate that the local lattice strain in the equiatomic CrMnFeCoNi HEA is anomalously large. Graphical abstract: Image 1